Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I've was asked to solve this (as homework):

$$2x + y + z = 3$$ $$4x + 2z = 10$$ $$2x + 2y = -2$$

I need to solve it with matrices and I have NO IDEA how to do so.

I need your help. thanks.

share|improve this question
2  
What have you learned so far? –  EuYu Nov 27 '12 at 22:05
1  
Hints: Can you write Aw = b? A is a 3x3 matrix (can you write out the equations using x, y, z)? What is b? How have you learned how to find a solution given this matrix form? Of course, maybe you have just learned some row-reduced echelon form and can do it that way and a half-dozen other ways too. –  Amzoti Nov 27 '12 at 22:07
1  
It's most unusual to assign homework on a topic not studied. Have you no notes on how the teacher said to do this? Have you no textbook to refer to? –  Gerry Myerson Nov 27 '12 at 22:14
    
@GerryMyerson I find that to be generally untrue, depending on the discipline and instructor. ;) –  Arkamis Nov 27 '12 at 22:39
add comment

4 Answers

up vote 0 down vote accepted

$$2x + y + z = 3 \tag{1}$$ $$4x + 2z = 10 \tag{2}$$ $$2x + 2y = -2 \tag{3}$$

A clever way to attack this problem is to note that we can divide through by $2$ for equation (2) to get $2x + z = 5$. Note that $2x+z$ is a part of equation (1), so we can rewrite (1) as:

$$5 + y = 3 \implies y = -2$$

Plug $y = -2$ into equation (3) to get: $$2x + 2(-2) = -2 \implies 2x = 2 \implies x = 1$$

Plug our known values for $x$ and $y$ into either equation (1) or (2) to find the value for $z$. I'll use equation (2).

$$4(1) + 2z = 10 \implies 2z = 6 \implies z = 3$$

share|improve this answer
    
Perfect answer, very clear to understand . How couldn't I think about it? thanks you very very much! –  Billie Nov 27 '12 at 22:51
    
No problem, glad to help. Feel free to click the up arrow to the left of an answer if you find it helpful :) –  Joe Nov 27 '12 at 23:01
    
I'd love to. But unfortunately I'm not allowed to do so duo to my low points sum.. –  Billie Nov 27 '12 at 23:16
    
But but but --- it says, "I need to solve it with matrices." This is a very good way to solve the system, but it doesn't answer the question as asked. –  Gerry Myerson Nov 27 '12 at 23:31
    
I thought it is the only way. but it doesn't - his way better. @GerryMyerson –  Billie Nov 27 '12 at 23:55
show 4 more comments

Your system of equations is equivalent to: $$ \left( \begin{array}{ccc} 2 & 1 & 1 \\ 4 & 0 & 2 \\ 2 & 2 & 0 \end{array} \right) \left( \begin{array}{c} x \\ y \\ z \end{array} \right) = \left( \begin{array}{c} 3 \\ 10 \\ -2 \end{array} \right). $$ You want to add/subtract multiples of the three rows (see Gaussian elimination) until you get to $$ \left( \begin{array}{ccc} 1 & 0 & 0 \\ 0 & 1 & 0 \\ 0 & 0 & 1 \end{array} \right) \left( \begin{array}{c} x \\ y \\ z \end{array} \right) = \left( \begin{array}{c} x \\ y \\ z \end{array} \right) = \left( \begin{array}{c} a \\ b \\ c \end{array} \right). $$

share|improve this answer
    
Angel - Thanks you! very helpful. –  Billie Nov 27 '12 at 22:54
add comment

You have:

$$A=\pmatrix{2&1&1\\4&0&2\\2&2&0}, b = \pmatrix{3\\10\\-2}$$

Do you know how to use the method of Gaussian elimination? If not, there are plenty of YouTube videos that demonstrate it. If you row reduce you get:

$$\pmatrix{1\\-2\\3}$$

as your solutions.

share|improve this answer
add comment

$\left( \begin{array}{ccc} 2 & 1 & 1 \\ 4 & 0 & 2 \\ 2 & 2 & 0 \end{array} \right) \left( \begin{array}{c} x \\ y \\ z \end{array} \right) = \left( \begin{array}{c} 3 \\ 10 \\ -2 \end{array} \right)$

Form the augmented matrix and then use the following row operations $R_2= 1/2R_2-R_1$ $R_3= R_3-R_1$, which gives the matrix as $\left( \begin{array}{ccc} 2 & 1 & 1 & 3 \\ 0 & -1 & 0 & 2 \\ 0 & 1 & -1 & -5 \end{array} \right)$

Then use the row operation $R_3 = R_3+R_2$ which gives the new matrix as $\left( \begin{array}{ccc} 2 & 1 & 1 & 3 \\ 0 & -1 & 0 & 2 \\ 0 & 0 & -1 & -3 \end{array} \right)$

Now use back substitution to get the results

share|improve this answer
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.